216k views
2 votes
A student is trying to solve the system of two equations given below:

Equation P: y + z = 6
Equation Q: 8y + 7z = 1

Which of the following is a possible step used in eliminating the y-term?

(y + z = 6) ⋅ −8
(y + z = 6) ⋅ 7
(8y + 7z = 1) ⋅ 7
(8y + 7z = 1) ⋅ 8

User Pilchard
by
5.3k points

2 Answers

5 votes

Answer:

(y+z=6)-8

Explanation:

You have to eliminate y. You already have 8y. What eliminates 8y? -8y. And if you simplify (y+z=6)-8, you’ll get -8y-8z=-48.

User Lars Noschinski
by
6.2k points
5 votes

Answer:

A. (y+z=6) -8

Explanation:

You will use the process of adding together the like terms. Since in equation Q, we have 8y, we need -8y in equation P. Answer A is the only one that will give us -8. You have to distribute -8 across all the variables and numbers in the parenthesis.

User Alex Spieslechner
by
5.4k points